infertility: psychological issues and counseling straegies - Leiblum, Sandra R (John Wiley&Sons,Inc, 1997)
Includes bibliographical references and index.; As the rate of infertility continues to climb worldwide, so does the need for psychological counseling among infertile individuals and couples attempting to cope with the pressures that infertility can bring to a relationship. At the same time, a bold new generation of fertility restoration, in-vitro fertilization, and surrogate parenting technologies have opened a Pandora's box of knotty ethical, moral, and psychological issues. Without the helping hand of a mental health professional, conflicts over these highly charged issues can tear apart relationships and cause considerable emotional and psychological suffering